Genre Trouble, Feel Tanks and Memetic Flailing - Chloe Turner; Rebecca Coleman (Media Theory)
This paper explores how Berlant’s concept of ‘genre flailing’ offers productive ways of understanding the circulation and sharing of memes during the Covid-19 pandemic. It focuses on our collaborative research project that deployed Feel Tanks to consider experiences of pandemic time, and specifically on how one participant unexpectedly responded to research prompts with a series of disjointed memes. Genre flailing refers to the thrashing around that happens when conventions and expectations about the world are paused or ruptured. Through the text, we grapple with the memes to explore their flailing as research data, as a response to the invitations extended in the Feel Tanks, as a popular pandemic medium, and more widely as a genre. We work with Berlant’s emphasis on embracing irresolution and their attentiveness to unfolding scenes of encounter which we argue offer valuable frameworks for sense-making with media and popular culture amidst crisis and uncertainty.